Developing English Language Competence through Content and Language Integrated Learning Approaches: Teachers' Perceptions of the Teaching Practice at the Bilingual Christian University of Congo - Mashauri, Mumbere Malonga; Muthambuko, John Mumbere (Journal of Education and Practice, 2023)
Purpose: This study gives an authentic sense to the use of CLIL as teachers experience it at UCBC. The central goal of the study is to describe the experience of permanent, visiting, international and ESOL teachers about the use of CLIL techniques in the process of developing UCBC students' English competences. The study puts much focus on teachers' perceptions on their professional development experiences on CLIL pedagogy in their teaching career. Methodology: The paradigm in which this study is situated is interpretivist and it used a qualitative study design. In fact, the study employed the descriptive approach to explore the perception of ESOL and content teachers regarding CLIL as a teaching technique at UCBC. Also, the descriptive approach helped in understanding how teachers are applying the CLIL technique and how they are adjusting themselves to the bilingual education practice. Findings: The result of the study showed that (1) teachers did not view themselves as language teachers; they did not know how they could design language objectives in order to incorporate the language items in their English content courses, (2) teachers did not understand how bilingual education pedagogy worked. Many of them did not know academic English and those who did, did not use English to teach their content courses, (3) teachers were prepared for the use of CLIL Pedagogy, but they were reluctant to implement it, (4) UCBC had no accountability policy related to using English to teach content. No one held them accountable for their students' content learning or language development, (5) teachers did not own the CLIL pedagogy and thought the development of students' English is the work of the English art department alone. Unique Contribution to Theory, Policy and Practice: The findings will put all the bilingual education stakeholders before their responsibility in the process of making UCBC a true and excellent bilingual academic institution. The authors recommended that UCBC content teachers be provided with a robust bilingual education training and a robust accountability policy. Also, department chairs should implement different decisions taken out of professional development sessions, and they should implement the bilingual education plan already put in place by the bilingual education coaches. Furthermore, UCBC bilingual education program should have strong and achievable outcomes/goals, and/or objectives for each department, and for each class including first undergraduate through fourth.